Feed force based optimization of process parameters by bio-nanofluid for machining SAE 1045 steel. (2022) - Gnanavel, C.; Saravanan, R.; Malladi, Avinash; Sekar, C.B.; Rajesh, S.; Nagarathi, D.K.
Highlights: Potential possibilities were investigated for machining the commercial shaft in conventional machining than CNC machine. Green machining and wet machining with nanofluid performance were compared with Feed force. Taguchi L16 experimental design and Taguchi optimization were employed. Parameters optimized based on the sense of feed force. Abstract: Waste generated from shop of Kerala Chips is utilized for preparing a novel Nano fluid. Such Nano fluid can be alternatively used for lubricating purpose for machining the precision shaft. This piece of research work investigating the effect of Nano fluid of Nano Nano-Boracic acid particles concentrated used coconut oil (Waste) in machining shat. The objective is analyzing the machinability performance and optimize process parameters based on the response of Feed force. Used coconut oil (Waste)/ Nano-Boracic acid particles, bio- Nanofluid synthesized and tested in semi-automated heavy-duty lathe. The cutting speed varied between 40 m/min to 190 m/min, the tool feed rate given in the rage of 0.05 mm/rev to 0.20 mm/rev as finish cut, the tool tip's nose radius varied from 0.30 mm to 1.20 mm. all three factors considered to feed at 4 levels so Taguchi L16 orthogonal array type experimental design utilized. Taguchi analysis, ANOVA and T -test used for analyzing results, study the factors influences and optimizing the process parameters. The finding was the proposed bio-nanofluid performance is found good and significant. The process parameters optimized and presented the factors and levels contribution in minimizing the feed force in the finishing the steel shaft.